Efeito do bloqueio dos receptores mineralocorticoides da região infra-límbica do córtex pré-frontal medial sobre a tolerância aos efeitos do midazolam em camundongos submetidos ao protocolo de teste e reteste no labirinto em cruz elevado - Mariano, Kairo Alan Albernaz (2017)
Several studies have shown that the previous experience (trial 1) to the elevated plus-maze (EPM) increases the avoidance of the open arms and impairs the anxiolytic-like effect of midazolam (MDZ), a benzodiazepine-GABAA receptor agonist, in a subsequent exposure (trial 2) to the maze, a phenomenon known as "one trial tolerance" (OTT). One hypothesis is that the learning generated in the first exposure allows a change in the strategy adopted by the animal. Considering that the infralimbic region (IL) of the medial prefrontal cortex (mPFC) would be involved in neuroendocrine modulation induced by stress, this study investigated the effects of intra-mPFC injection (region IL) of RU28318 (mineralocorticoid receptor antagonist, MR) in the memory acquisition and consolidation phase, in the tolerance to MDZ effects in mice exposed to the trial 1 and trial 2 in the LCE. Male Swiss mice (n = 8-12 per group) were used, and when necessary, bilateral cannulae were surgically implanted bilaterally in the IL region of the mPFC. Experiment 1: The animals of each group received intraperitoneal (i.p.) injection of saline or MDZ (2mg/kg) and after 30 minutes were exposed to trial 1 for 5 minutes in the EPM. After 24 hours, the mice received either systemic injection of saline or MDZ (2mg/kg) and 30 minutes later they were individually exposed to trial 2 in the LCE for 5 minutes. Experiment 2 (acquisition phase): After four days of recovery the subjects of each group received intra-mPFC injection of vehicle or RU28318 (5 ou 10ng/0,1μl) and were exposed to trial 1 for 5 minutes. After 24 hours, each mouse received systemic injection (intraperitoneal, i.p.) of saline or midazolam (2mg/kg) and 30 minutes later was individually exposed to the Trial 2. Experiment 3 (consolidation phase): After four days of recovery the subjects of each group were exposed to the EPM test for 5 minutes and subsequently received intra-mPFC injection of vehicle or RU28318 (5 or 10ng/0.1μl). After 24 hours, the mice received either systemic injection of vehicle or MDZ (2mg/kg) and 30 minutes later they were individually exposed to trial 2 in the EPM for 5 minutes. The injection MDZ produced anxiolytic-like effect in animals exposed to the trial 1 to the EPM, characterized by increased exploration in the open arms and reduction of risk assessment behaviors without affecting the locomotor activity. This effect was abolished in the retest, confirming the OTT. Two-way ANOVA that intra-mPFC infusion of RU28318 did not modify any behavior in trial 1. However, it was observed that when administered prior to EPM, it reestablished the anxiolytic effect of MDZ administered prior to retest. When infused after the test period, RU28318 did not modify the OTT phenomenon for the MDZ. The MR antagonism in the IL region of the mPFC, seems to interfere with the memory acquisition phase but not the consolidation phase. Thus, we suggest that MR blockade of the IL region of the mPFC may interfere with the acquisition, but not the consolidation, appropriate information during trial, influencing the OTT phenomenon.